Increasing Activity and Learning Outcomes of Class Xi Tkj A Smk Muhammadiyah 1 Moyudan in Network Service Technology Subjects Through the Tai Learning Model (Team Accelerated Instruction) - Yazid Afifudin Abror (Jurnal Mandiri IT, 2021)
This study aims to increase the activeness and learning outcomes of class XI TKJ A SMK Muhammadiyah 1 Moyudan in the subject of network service technology using the TAI (Team Accelerated Instruction) learning model. The data collection method in this study used the method of observation, learning outcomes tests, and documentation. This analysis is applied by processing the activity scores and the average student learning outcomes test scores, calculating the percentage, presenting the data, then drawing conclusions. The most prominent increase occurred in mental activity which increased by 20.60%. This is evidenced by the percentage of student activity at the end of the cycle is 80.43%, which means an increase from the initial data or baseline (51.19%). At the end of the cycle, the average score of students was 79.14, which means an increase from the initial data or baseline (66). The most prominent increase occurred in mental activity which increased by 20.60%. The conclusion obtained based on this research is that the implementation of the TAI (Team Accelerated Instruction) cooperative learning model can increase student activity and student learning outcomes. This is evidenced by the percentage of student activity at the end of the cycle is 80.43%, which means an increase from the initial data or baseline (51.19%). At the end of the cycle, the average score of students was 79.14, which means an increase from the initial data or baseline (66). The most prominent increase occurred in mental activity which increased by 20.60%. 43% which means an increase from the initial data or baseline (51.19%). At the end of the cycle, the average score of students was 79.14, which means an increase from the initial data or baseline (66). The most prominent increase occurred in mental activity which increased by 20.60%. 43% which means an increase from the initial data or baseline (51.19%). At the end of the cycle, the average score of students was 79.14, which means an increase from the initial data or baseline (66). The most prominent increase occurred in mental activity which increased by 20.60%.